Climate change and health of the urban poor: The role of environmental justice - Divya Chaudhry (Elsevier, 2024)
Direct effects of climate change on health, such as a rise in the incidence of heat strokes due to summer heatwaves, and indirect health effects such as under-nutrition due to a rise in food prices because of climate change, are mediated through the social and environmental determinants of health (SEDH), which include but are not limited to potable water, clean air, adequate sanitation, safe shelter, and adequate food. Based on a narrative review, this paper identifies possible mechanisms through which human health is impacted by climate change. Evidence has shown that climate change-induced effects such as high temperatures and heat waves, Water, Sanitation and Hygiene (WASH), vector-borne diseases and undernutrition lead to undesirable health outcomes for the urban poor through unfavorable SEDH. Given that health of the urban poor is anticipated to be disproportionately affected by the risks of changing climate, this paper emphasizes the need for focusing on the environmental justice approach to safeguard the health of the urban poor in developing countries. It also argues for strengthening participatory and transparent urban governance to upgrade informal settlements and address factors that enhance health vulnerabilities of the urban poor. It contributes to the limited literature on environmental justice in the context of developing countries and provides a rationale behind mainstreaming the environmental justice approach for reducing the climate change-induced health risks for the urban poor.